RANCANGAN UNDANG-UNDANG MAHKAMAH AGUNG (RUU MA) : PENGKAJIAN FILOSOFI, SEJARAH, ASAS, NORMA DALAM DINAMIKA PERKEMBANGAN KETATANEGARAAN INDONESIA - Bhakti, Teguh Satya (Jurnal Hukum dan Peradilan, 2014)
Parliament proposed initiative to change back the bill MA for three (3) foundation: first, the desire of the House to form a Supreme Court that can carry kekusaan judiciary to realize the state of law and achieve the objectives of the state, second, the Law on the current MA , seen there are still weaknesses. Third, awareness of the need for harmonization and synchronization with the MA bill to be prepared with due regard to the interests of law enforcement and justice must be directly in line with the interests of law and public justice. According to the analysis, the substance of the bill by parliament yet the Supreme Court in accordance with the principles of independent judicial power, especially concerning: First, the House Oversight Against MA; Second, the Supreme Court decision setting tengang substance (Article 97), which not only violates the independency of the judiciary, but also waives the rule of law; Third, criminalization judge if the judge violated or ignored the Article 94 jo. Article 96; Fourth, the organizational structure of the secretariat of the Supreme Court (Article 35) causes a buildup of duties, functions and authority of the Secretariat tremendous MA; Fifth, the Material Test Procedure Law Rights (Article 90 paragraph (8)) are not further described; Sixth, Room Sharing Case that cause fattening of human resources in the rate and with the same duties and functions by the Clerk of the Supreme Court; and Seventh, Minimum Age Limits for Supreme Court Justices. Keywords: Bill, the Supreme Court, constitutional development